Construction of Agency within Climate Change Framing in Media Discourse: a Corpus-Based Study - Kramar, Natalie (Respectus Philologicus, 2023)
The study addresses the role of linguistic agency in framing climate change in media discourse based on the corpus of 75 articles from leading British and American news outlets. We have used corpus manager AntConc to analyse the linguistic context of the phrase climate change and alternative terms (climate crisis, climate emergency, etc.) when positioned as an agent vs a recipient of the process. Both metaphorical and non-metaphorical framing patterns have been identified, with the discussion of their broad social implications. We have revealed that climate change is routinely represented as a contributor towards negative situations of different kinds but rarely as a direct and exclusive cause. This may divert the readership’s attention from the urgency of the problem, as its salience is not underscored enough. The most important finding is that climate change is frequently associated with humanlike agency, presented as an evil-doer or an enemy that must be fought. We argue that this framing is problematic as it backgrounds humans’ responsibility for causing and exacerbating climate change.
Keywords: climate change; framing; agency; media discourse; metaphor